제페토 메타버스를 활용한 진로탐색 미술프로그램에 관한 연구 - 배애진(Ae-Jin Bae); 허윤정(Yoon-Jung Huh) (디지털콘텐츠학회논문지, 2023)
본 연구는 메타버스 중 하나인 제페토를 활용하여 중학교 진로탐색 미술프로그램 개발을 제안하였으며 그 효과성을 사전·사후 설문지 검사와 사후 인터뷰 분석을 통해 검증하였다. 미술프로그램은 중학생 4명을 대상으로 7차시에 걸쳐 진행했으며, 분석 준거로는 진로정체감과 진로성숙도이며 그 결과는 다음과 같다. 첫째, 제페토를 활용한 진로 탐색 미술 프로그램은 학습자들의 진로정체감과 진로성숙도 점수 향상에 효과가 있었다. 진로정체감 하위요인 중에서는 독립성과 자기존재의식, 목표 지향성에서 유의미한 변화가 나타났다. 진로성숙도 하위요인 중에서는 계획성, 정보탐색, 합리적 의사결정에서 유의미한 변화가 나타났다. 둘째, 인터뷰 분석 결과 제페토를 통한 사실적이고 구체적인 직업 공간의 시각화는 학생들에게 높은 만족감을 주었고, 진로와 꿈을 자극하는 교육적 촉매제였다. 이는 진로에 대한 관심을 갖게 하거나 진로에 대한 목표를 구체화하여 학생들의 진로정체감과 진로성숙도에 긍정적인 영향을 주었다. In this study, we developed a career exploration art program using ZEPETO, and verified its effectiveness through pre- and post-questionnaire tests and post-interview analysis. The art program was conducted over seven sessions targeting four students from middle school. The criteria for analysis were career identity and career maturity, and the results were as follows: first, the program was effective in improving the career identity and career maturity of the learner. Notably, within the sub-factors of career identity, significant changes were found in independence, self-existence, and goal orientation. Similarly, among the sub-factors, significant changes were found in planning, information search, and rational decision-making. Second, as a result of interview analysis, the visualization of realistic and specific job space through ZEPETO provided students a high level of satisfaction and was an educational catalyst that stimulated their careers and dreams. This had a positive effect on the career identity and career maturity of students owing to the raised interest in careers or specifying career goals. KCI Citation Count: 2